Chicken lens development: complete signature of expression of galectins during embryogenesis and evidence for their complex formation with α-, β-, δ-, and [tau]-crystallins, N-CAM, and N-cadherin obtained by affinity chromatography - García Caballero, Gabriel; Schmidt, Sebastian; Manning, Joachim C.; Michalak, Malwina; Schlötzer-Schrehardt, Ursula; Ludwig, Anna-Kristin; Kaltner, Herbert; Sinowatz, Fred; Schnölzer, Martina; Kopitz, Jürgen; Gabius, Hans-Joachim (Cell & tissue research, 2020)
The emerging multifunctionality of galectins by specific protein-glycan/protein interactions explains the interest to determine their expression during embryogenesis. Complete network analysis of all seven chicken galectins (CGs) is presented in the course of differentiation of eye lens that originates from a single type of progenitor cell. It answers the questions on levels of expression and individual patterns of distribution. A qualitative difference occurs in the CG-1A/B paralogue pair, underscoring conspicuous divergence. Considering different cell phenotypes, lens fiber and also epithelial cells can both express the same CG, with developmental upregulation for CG-3 and CG-8. Except for expression of the lens-specific CG (C-GRIFIN), no other CG appeared to be controlled by the transcription factors L-Maf and Pax6. Studying presence and nature of binding partners for CGs, we tested labeled galectins in histochemistry and in ligand blotting. Mass spectrometric (glyco)protein identification after affinity chromatography prominently yielded four types of crystallins, N-CAM, and, in the cases of CG-3 and CG-8, N-cadherin. Should such pairing be functional in situ, it may be involved in tightly packing intracellular lens proteins and forming membrane contact as well as in gaining plasticity and stability of adhesion processes. The expression of CGs throughout embryogenesis is postulated to give meaning to spatiotemporal alterations in the local glycome.